Correlation of Sustainability Report Disclosure Towards Financial Firm Performance in Indonesia, Malaysia & Singapore Palm Oil Sector from 2020 to 2024 - Jippanola, Adimas Jagad; Faturohman, Taufik (Journal Research of Social Science, Economics, and Management, 2026)
This research examines the impact of sustainability performance on the financial performance of 26 publicly listed palm oil companies in Indonesia, Malaysia, and Singapore during 2020–2024, using 130 firm-year observations. The research addresses the increasing pressure on the palm oil sector to balance economic growth with environmental and social responsibility. Sustainability disclosure is measured through the ESG Score to evaluate whether strong ESG practices contribute to financial performance or merely represent compliance costs. The study applies a panel data approach, with the Random Effects (RE) Model selected as the most appropriate estimation technique based on the Hausman and Breusch–Pagan Lagrange Multiplier tests. The results indicate that sustainability disclosure has a positive and significant effect on financial performance. The ESG Score shows coefficients of 0.282 for Net Profit Margin (NPM) and 0.329 for Revenue Growth, both significant at the 1% level (p = 0.000), supporting H1 and H2. Meanwhile, firm size does not significantly influence either financial performance indicator, suggesting that sustainability maturity and strategic ESG integration are more important than asset scale. The findings demonstrate that integrating ESG principles into business strategies provides financial benefits by improving profitability and supporting revenue expansion. Furthermore, younger firms appear to be more responsive in achieving revenue growth, while older firms show slight advantages in maintaining profit margins. This research highlights ESG integration as a strategic investment that can create sustainable competitive advantages in the highly scrutinized palm oil industry.